Multi-year record of atmospheric and snow surface nitrate in the central Antarctic plateau. (April 2017) - Traversi, R.; Becagli, S.; Brogioni, M.; Caiazzo, L.; Ciardini, V.; Giardi, F.; Legrand, M.; Macelloni, G.; Petkov, B.; Preunkert, S.; Scarchilli, C.; Severi, M.; et al.
Abstract: Continuous all year-round samplings of atmospheric aerosol and surface snow at high (daily to 4-day) resolution were carried out at Dome C since 2004-05 to 2013 and nitrate records are here presented. Basing on a larger statistical data set than previous studies, results confirm that nitrate seasonal pattern is characterized by maxima during austral summer for both aerosol and surface snow, occurring in-phase with solar UV irradiance. This temporal pattern is likely due to a combination of nitrate sources and post-depositional processes whose intensity usually enhances during the summer. Moreover, it should be noted that a case study of the synoptic conditions, which took place during a major nitrate event, showed the occurrence of a stratosphere-troposphere exchange. The sampling of both matrices at the same time with high resolution allowed the detection of a an about one-month long recurring lag of summer maxima in snow with respect to aerosol. This result can be explained by deposition and post-deposition processes occurring at the atmosphere-snow interface, such as a net uptake of gaseous nitric acid and a replenishment of the uppermost surface layers driven by a larger temperature gradient in summer. This hypothesis was preliminarily tested by a comparison with surface layers temperature data in the 2012-13 period. The analysis of the relationship between the nitrate concentration in the gas phase and total nitrate obtained at Dome C (2012-13) showed the major role of gaseous HNO3 to the total nitrate budget suggesting the need to further investigate the gas-to-particle conversion processes. Highlights: Continuous nitrate records in aerosol and snow obtained at Dome C for multiple years. One-month lag of nitrate summer maxima in snow with respect to aerosol was observed. Gaseous phase was found to be the most relevant contribution to nitrate budget at Dome C. Synoptic analysis of a major nitrate event showed a stratosphere-troposphere exchange. Uptake of atmospheric HNO3 and bottom-up processes can explain snow summer maxima.